International Migrant Students: An Analysis of the Conditions of Access and Retention in Brazilian Basic Education (Interdisciplinary Studies Journal, 2024)
This article is an excerpt from a doctoral research developed by the Postgraduate Program in Education at the Federal University of Mato Grosso do Sul (PPGEdu/UFMS). It is a qualitative investigation aimed at presenting the conditions of access and retention of international migrant students in basic education in Brazil. To do so, it presents data on the expansion of recent migration flows, as well as on the student population in this condition. It also presents legal provisions related to the entry and stay of people in an immigration situation in the country, as well as those specifically addressing access to education. With this in mind, the article analyzes the issues at hand from the perspective of Foucauldian studies, particularly focusing on the notion of disciplinary power and its implications for educational policies in a migration context, or even the absence of such policies, and the potential effects on the retention of these students in educational institutions. The research aims to expand the discussions on the power mechanisms that operate within educational policies, highlighting the inconsistencies between access conditions and the quality of retention of these students in schools.
Keywords: International Migrations; School; Education